Toward Precision Oncology in Glioblastoma with a Personalized Cancer Genome Reporting Tool and Genetic Changes Identified by Whole Exome Sequencing - ERDOĞAN, ONUR; ERZİK, CAN; ARĞA, KAZIM YALÇIN; BAYRAKLI, FATİH (My University, 2023)
Precision/personalized medicine in oncology has two key pillars: molecular profiling of the tumors and personalized reporting of the results in ways that are clinically contextualized and triangulated. Moreover, neurosurgery as a field stands to benefit from precision/personalized medicine and new tools for reporting of the molecular findings. In this context, glioblastoma (GBM) is a highly aggressive brain tumor with limited treatment options and poor prognosis. Precision/personalized medicine has emerged as a promising approach for personalized therapy in GBM. In this study, we performed whole exome sequencing of tumor tissue samples from six newly diagnosed GBM patients and matched nontumor control samples. We report here the genetic alterations identified in the tumors, including single nucleotide variations, insertions or deletions (indels), and copy number variations, and attendant mutational signatures. Additionally, using a personalized cancer genome-reporting tool, we linked genomic information to potential therapeutic targets and treatment options for each patient. Our findings revealed heterogeneity in genetic alterations and identified targetable pathways, such as the PI3K/AKT/mTOR pathway. This study demonstrates the prospects of precision/personalized medicine in GBM specifically, and neurosurgical oncology more generally, including the potential for genomic profiling coupled with personalized cancer genome reporting. Further research and larger studies are warranted to validate these findings and advance the treatment options and outcomes for patients with GBM.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Genetics; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Mikrobiyoloji; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; GENETİK VE KALITIM; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; GENETICS & HEREDITY; Biyokimya; Moleküler Tıp; Moleküler Biyoloji; Genetik; Biochemistry; Molecular Medicine; Molecular Biology; Genetics; genomics; glioblastoma; personalized medicine; precision oncology; whole exome sequencing